Comparative analysis of differential gene expression indicates divergence in ontogenetic strategies of leaves in two conifer genera. Issue 2 (16th February 2022) - Webster, Cynthia; Figueroa‐Corona, Laura; Méndez‐González, Iván David; Álvarez‐Soto, Lluvia; Neale, David B.; Jaramillo‐Correa, Juan Pablo; Wegrzyn, Jill L.; Vázquez‐Lobo, Alejandra
Abstract: In land plants, heteroblasty broadly refers to a drastic change in morphology during growth through ontogeny. Juniperus flaccida and Pinus cembroides are conifers of independent lineages known to exhibit leaf heteroblasty between the juvenile and adult life stage of development. Juvenile leaves of P. cembroides develop spirally on the main stem and appear decurrent, flattened, and needle‐like; whereas adult photosynthetic leaves are triangular or semi‐circular needle‐like, and grow in whorls on secondary or tertiary compact dwarf shoots. By comparison, J. flaccida juvenile leaves are decurrent and needle‐like, and adult leaves are compact, short, and scale‐like. Comparative analyses were performed to evaluate differences in anatomy and gene expression patterns between developmental phases in both species. RNA from 12 samples was sequenced and analyzed with available software. They were assembled de novo from the RNA‐Seq reads. Following assembly, 63, 741 high‐quality transcripts were functionally annotated in P. cembroides and 69, 448 in J. flaccida . Evaluation of the orthologous groups yielded 4140 shared gene families among the four references (adult and juvenile from each species). Activities related to cell division and development were more abundant in juveniles than adults in P. cembroides, and more abundant in adults than juveniles in J. flaccida . Overall, there were 509 up‐regulated and 81 down‐regulated genes in the juvenile condition of P. cembroides and 14 up‐regulated and 22 down‐regulated genes in J. flaccida . Gene interaction network analysis showed evidence of co‐expression and co‐localization of up‐regulated genes involved in cell wall and cuticle formation, development, and phenylpropanoid pathway, in juvenile P. cembroides leaves. Whereas in J. flaccida, differential expression and gene interaction patterns were detected in genes involved in photosynthesis and chloroplast biogenesis. Although J. flaccida and P. cembroides both exhibit leaf heteroblastic development, little overlap was detected, and unique genes and pathways were highlighted in this study. Abstract : Juniperus flaccida and Pinus cembroides exhibit leaf heteroblasty between the juvenile and adult life stage of development. Comparative analyses were performed to evaluate differences in anatomy and gene expression patterns between developmental phases in both species.